2000
DOI: 10.1007/bf02988212
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of99mTc-tetrofosmin,99mTc-MIBI and201TI in malignant thymoma

Abstract: 99mTc-tetrofosmin, Thallium-201-chloride (201Tl) and 99mTc-MIBI imagings were performed in a patient with malignant thymoma. Tracer uptake in the primary tumor was demonstrated. The tumor-to-background ratios of planar and SPECT imagings were 1.60 and 1.98 for 99mTc-tetrofosmin, 1.12 and 2.09 for 201Tl, and 1.19 and 1.80 for 99mTc-MIBI, respectively. In another patient 99mTc-tetrofosmin and 201Tl imagings were performed. Not only the primary tumor but also the direct invasions and metastatic lesions (bone meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Our data are consistent with other literature findings. The UR values calculated in our studies were in the same range with the values of Hashimoto et al studies (13) and moderate higher then the values calculated by Fiorelli et al (28) on a number of mediastinal tumors including thymoma. These different results between studies can be explained by particularities in image processing and quantification: firstly, if the UR is calculated on whole tumor mass, on planar images, or on SPECT slices, between maximum or mean uptake values; secondly, if the normal region is chosen on a lung region, having the lowest background or on a mediastinal region; thirdly, if the quantification is made on images acquired early or at 60 minutes, the last interval of time being demonstrated, by in vitro studies, to correspond to the highest 99m Tc MIBI cellular uptake influx, for culture cells, like myocites and different cancer cells (18,19), so possibly also for thymus tumoral cells.…”
Section: B) Thymoma Cellularity Role In Explaining Tumor Tissue Radiosupporting
confidence: 85%
See 1 more Smart Citation
“…Our data are consistent with other literature findings. The UR values calculated in our studies were in the same range with the values of Hashimoto et al studies (13) and moderate higher then the values calculated by Fiorelli et al (28) on a number of mediastinal tumors including thymoma. These different results between studies can be explained by particularities in image processing and quantification: firstly, if the UR is calculated on whole tumor mass, on planar images, or on SPECT slices, between maximum or mean uptake values; secondly, if the normal region is chosen on a lung region, having the lowest background or on a mediastinal region; thirdly, if the quantification is made on images acquired early or at 60 minutes, the last interval of time being demonstrated, by in vitro studies, to correspond to the highest 99m Tc MIBI cellular uptake influx, for culture cells, like myocites and different cancer cells (18,19), so possibly also for thymus tumoral cells.…”
Section: B) Thymoma Cellularity Role In Explaining Tumor Tissue Radiosupporting
confidence: 85%
“…Even radiotracers functional images have been reported to be useful for thymoma diagnosis from a number of studies (13)(14)(15)(16)(17), the techniques and, consequently, the results are relatively heterogeneous and fewer authors explained clearly what the tumor To explain the obtained results it is necessary to: a) start from the known data about the structure of 99m Tc MIBI and its cellular uptake mechanism, and b) correlate these data with histopathological structure of the thymus, in order to understand why and when thymoma cells show high radiotracer uptake.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, 99mTcMIBI scintigraphy showed accumulation that was consistent with a 4.5 cm substantial tumour, and pathology showed that the tumour was a Type B2 thymoma. The mechanism of accumulation in the thymoma has not been clearly elucidated, although it is believed to be closely related to the thymoma, since the inferior parathyroid organs arise from the third pharyngeal cone adjacent to the thymic organs during the embryonic period 3 . In addition, most thymomas occur in the anterior mediastinum, and about 4% occur in the neck, middle or posterior mediastinum 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of accumulation in the thymoma has not been clearly elucidated, although it is believed to be closely related to the thymoma, since the inferior parathyroid organs arise from the third pharyngeal cone adjacent to the thymic organs during the embryonic period. 3 In addition, most thymomas occur in the anterior mediastinum, and about 4% occur in the neck, middle or posterior mediastinum. 4 Among them, reports of cases complicated by myasthenia gravis are quite rare.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with rapid tumor proliferation, high metabolism and low tissue differentiation normally exhibited high uptake of 99m Tc-MIBI in the early phase (18,19). Fiorelli et al (17) reported that the uptake of MIBI by thymoma was increased with the increasing degree of malignancy of the tumor (the T/N values of type A, B and C were 1.3±0.2,1.8±0.3 and 2.7±0.5, respectively).…”
Section: Discussionmentioning
confidence: 99%